PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI MEDIASI PADA PENGGUNA APLIKASI E COMMERCE BLIBLI - Dehantiansah; Mike Yolanda (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
In the digital age, e-commerce is becoming one of the main pillars of the modern economy, where service quality plays a crucial role in creating a superior customer experience. Blibli, as one of the leading e-commerce platforms in Indonesia, faces challenges in maintaining customer loyalty amid fierce market competition. This study aims to analyze the influence of Service Quality on Customer Loyalty with Customer Satisfaction as a mediating variable in users of the Blibli e-commerce application. The research approach uses a quantitative method by collecting data through questionnaires through Gform and involving 180 respondents who are active users of the Blibli application, and then processed using the SmartPLS application v.4.0.9.9. The results of the study show that: (1) Service Quality has a positive and significant effect on Customer Satisfaction, with Service Quality dimensions such as efficiency, content, fulfillment, responsiveness, and contact. (2) Service Quality has a Positive and Significant Effect on Customer Loyalty, (3) Customer Satisfaction has a Positive and Significant Effect on Customer Loyalty on Service Quality